2011
DOI: 10.1016/j.jmb.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Aβ1–42 Toxicity Inhibition by Aβ C-Terminal Fragments: Discrete Molecular Dynamics Study

Abstract: Amyloid β-protein (Aβ) is central to the pathology of Alzheimer’s disease (AD). Of the two predominant Aβ alloforms, Aβ1–40 and Aβ1–42, the latter forms more toxic oligomers. C-terminal fragments (CTFs) of Aβ were recently shown to inhibit Aβ1–42 toxicity in vitro. Here we studied Aβ1–42 assembly in the presence of three effective CTF inhibitors and an ineffective fragment, Aβ21–30. Using a discrete molecular dynamics approach that recently was shown to capture key differences between Aβ1–40 and Aβ1–42 oligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 58 publications
10
61
0
1
Order By: Relevance
“…The first DMD4B-HYDRA study of Aβ 40 and Aβ 42 oligomer formation showed that Aβ 42 oligomers are characterized by increased plasticity in the N-terminal region relative to Aβ 40 oligomers [44], the feature that was hypothesized to be linked to increased toxicity of Aβ 42 relative to Aβ 40 oligomers [48]. This result was unexpected because the sequences of Aβ 40 and Aβ 42 differ by two additional amino acids, IA, at the C-terminus of the latter, so that structural differences would be expected to occur in the C-terminal region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first DMD4B-HYDRA study of Aβ 40 and Aβ 42 oligomer formation showed that Aβ 42 oligomers are characterized by increased plasticity in the N-terminal region relative to Aβ 40 oligomers [44], the feature that was hypothesized to be linked to increased toxicity of Aβ 42 relative to Aβ 40 oligomers [48]. This result was unexpected because the sequences of Aβ 40 and Aβ 42 differ by two additional amino acids, IA, at the C-terminus of the latter, so that structural differences would be expected to occur in the C-terminal region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the present study, Aβ 40 is the only variant that forms oligomers, which lack the conformations with extended N-to-C distances, whereby both substitutions, [K16A] and [K28A], cause changes in the N-terminal secondary structure of Aβ 40 oligomers that are similar to those induced by previously reported Aβ 40 sequence modifications described above. The question that remains to be explored is whether or not increased plasticity at the N-termini of Aβ 42 oligomers plays a role in Aβ 42 -mediated toxicity [48].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For most proteins in an aqueous solution, E HP is expected to be of a similar value. We thus use here E HP = 0.3, which corresponds to E HP = 1.4 kcal/mol or 2.3 k B T, the value that was used in the Aβ studies of folding and oligomerization [16,19,23]. The solvent parameter associated with effective electrostatic interactions, E CH , was varied between 0 and 1 (see Section 3.1) to explore the effect of ionic strengths on folding.…”
Section: Units and Implicit Solvent Parametersmentioning
confidence: 99%